2022
DOI: 10.1101/2022.08.02.502350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Primary Somatosensory Cortex Bidirectionally Modulates Sensory Gain and Nociceptive Behavior in a Layer-Specific Manner

Abstract: The primary somatosensory cortex (S1) is the hub for body sensation of both innocuous and noxious signals, yet its role in somatosensation versus pain is debated. Despite known contributions of S1 to sensory gain modulation, its causal involvement in subjective sensory experiences remains elusive. Unspecific bulk manipulations of S1 activity have not disambiguated the precise role of the S1 in nociception and pain. Here, using cell-type-specific manipulations in mouse S1 we reveal the involvement of two major … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…We confirmed the increased activity of M1 corticospinal neurons during our wheel turning task as well as locomotion by using a retrograde labeling approach from the cervical spinal cord (Figure S11A) and imaging the dendritic dynamics of this population through a cranial window. In both wheel turning and walking, the activity of this population was positively correlated with movement (Figure 5A,B Given the opposing activity of these two populations, we hypothesized that M1 CT neurons could drive feedforward inhibition of corticospinal neurons in a similar circuit configuration to that reported in other cortical regions such as visual cortex 51,52 and somatosensory cortex 53,54 . In this model, suppression of M1 CT neurons would release feedforward inhibition and allow for increased corticospinal activity.…”
Section: M1 Ct Regulation Of M1 Corticospinals Scales With Learningmentioning
confidence: 75%
“…We confirmed the increased activity of M1 corticospinal neurons during our wheel turning task as well as locomotion by using a retrograde labeling approach from the cervical spinal cord (Figure S11A) and imaging the dendritic dynamics of this population through a cranial window. In both wheel turning and walking, the activity of this population was positively correlated with movement (Figure 5A,B Given the opposing activity of these two populations, we hypothesized that M1 CT neurons could drive feedforward inhibition of corticospinal neurons in a similar circuit configuration to that reported in other cortical regions such as visual cortex 51,52 and somatosensory cortex 53,54 . In this model, suppression of M1 CT neurons would release feedforward inhibition and allow for increased corticospinal activity.…”
Section: M1 Ct Regulation Of M1 Corticospinals Scales With Learningmentioning
confidence: 75%
“…Although CT feedback circuits are ubiquitous across mammalian species and modalities (Hasse and Briggs, 2017b;Shepherd and Yamawaki, 2021), a thorough understanding of CT functions remains elusive. Indeed, previous studies suggest several functions (Contreras et al, 1996;Temereanca and Simons, 2004;Wang et al, 2006;Andolina et al, 2007;Li and Ebner, 2007;Olsen et al, 2012;Mease et al, 2014;Denman and Contreras, 2015;Hasse and Briggs, 2017a;Pauzin and Krieger, 2018;Wang et al, 2018;Pauzin et al, 2019;Ansorge et al, 2020;Born et al, 2021;Ziegler et al, 2023). This lack of understanding is likely due to complex CT circuit interactions, the nature of which is only beginning to emerge.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also showed that the combined use of EA and chemogenetic astrocyte activation potentiated the suppression of acid-induced acute hyperalgesia by EA. This brings us to the layer specificity of the cortex, as different layers may have opposite effects on pain control (6). Hence, ST36-mediated EA analgesia may rely on the astrocytic activation of one of the layers in S1HL, with some likelihood that of L5.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is an unpleasant signal that is associated with tissue damage and involvement of different brain structures, some of which are part of the pain matrix, including the primary somatosensory cortex (S1), primary motor and supplementary motor cortices, secondary somatosensory cortex, anterior cingulate cortex, insular cortex, prefrontal cortex, thalamus, amygdala, and hippocampus (1)(2)(3)(4)(5)(6)(7)(8)(9). Each of these regions plays a distinct role in different aspects of pain perception, such as the sensory, emotional, and cognitive dimensions of pain (10-12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation